Culex pipiens sperm motility is initiated by a trypsin‐like protease from male accessory glands. Issue 5 (17th April 2018) - Stephens, Kimberly; Cardullo, Richard A.; Thaler, Catherine D.
Abstract : In most animals, sperm are stored in a quiescent state in the male reproductive tract and only initiate motility when released into either the female reproductive tract, or, in the case of broadcast spawners, the external environment. Male accessory gland secretions transferred into the female reproductive tract may provide factors that modulate sperm viability and storage, or aid in sperm competition, as well as activate sperm motility. In several insects, serine proteases have been implicated in activating sperm motility. Our previous studies have shown that, in Culex quinquefasciatus, either a male accessory gland extract or purified trypsin is sufficient to initiate sperm motility in vitro. The objective of this study was to identify and characterize trypsin‐like enzymes produced in the Culex male accessory glands. Mass spectrometry was used to analyze accessory gland proteins and this preliminary proteomic analysis identified 4 trypsin‐like proteases (trypsin, trypsin4, and two trypsin7 isoforms). When measured with the chromogenic trypsin substrate Na ‐benzoyl‐L‐arginine‐ethyl‐ester‐hydrochloride (BAEE), trypsin‐like protease activity in the accessory glands was robust, with a pH optimum of 8. The pH range for the Culex trypsin activity was substantially narrower than a mammalian homologue (porcine pancreatic trypsin). A soybean trypsin inhibitor (SBTI) ‐agarose affinity column was used to independently identify trypsin‐like accessory gland proteins. Several proteins were enriched in the eluate, as detected by silver staining of SDS–PAGE gels. Taken together, these data demonstrate the presence of trypsin‐like activity and several trypsin‐like proteins in the Culex male accessory glands.